(untitled) - Dieter, George E . (New York, 2013)
Engineering Design provides the senior mechanical engineering students with a realistic understanding of the design process. It is written from the viewpoint that design is the central activity of the engineering profession, and it is more concerned with developing attitudes and approaches than in presenting design techniques and tools.
Keywords: Kỹ thuật thiết kế,Engineering design